Investigating Whether Consuming Meals in a Dining Room Impacts Patients’ Mood, Level of Interaction, and Subsequent Nutrient Intake in a Stroke Rehabilitation Ward. - Sali Abouhajar; Grace Bennett; Linda Dooley; Tracy Waldron; Katie Walsh; Sile Murphy; Aoibheann McMorrow; Joseph Harbison; Suzanne L Doyle (SURE Journal: (Science Undergraduate Research Experience Journal))
Background/objectivesMalnutrition is evident in hospitals and stroke patients are at increased risk. Protected mealtimes may help increase nutrient intake especially when patients interact and enjoy the dining room atmosphere. The aim of this research is to investigate if eating in a communal dining room increases nutritional intake compared to eating at the bedside and to investigate whether patient interaction and mood affects patient nutrient intake. Population/methods:A randomised cross-sectional study of 20 patients, assessing a comparison of patient’s mealtime consumption at lunchtime in the dining room and at the beside. Patients’ meals were weighed before and after consumption as well as an estimated percentage of their meals consumed. Patients’ interaction was observed and noted using a modified case report form. The Hammond depression scale was used to score patients’ mood. Patient and staff satisfaction surveys were completed at the end of the study period. Results:There was no significant difference in protein and energy consumption in the dining room (16.4g protein and 379.2kcal) compared to at the bedside (13.2g protein and 333.8kcal), p=0.160 and p=0.110 respectively. Interaction was higher in the dining room. The percentage mealtime consumption increased the more interactive a patient was from a mean of 74% in less interactive patients to 98% in highly interactive patients (p=0.193). There was no significant association between depression score and mealtime consumption. All 19 patients enjoyed eating in the dining room and 14 out of the 19 patients preferred eating in the dining room. Conclusion:Further studies are required to explore how intake can be improved among stroke rehabilitation patients.